Comparison of Hematopoietic Stem Cell Transplantation Outcomes Using Matched Sibling Donors, Haploidentical Donors, and Immunosuppressive Therapy for Patients With Acquired Aplastic Anemia - Zhang, Yuanfeng; Huo, Jiali; Liu, Li; Shen, Yuyan; Chen, Juan; Zhang, Tingting; Chen, Xin; Pang, Aiming; Yang, Donglin; Zhang, Rongli; Ma, Qiaoling; Zhai, Weihua; et al. (Frontiers in Immunology, 2022)
We retrospectively compared the outcomes of 387 consecutive patients with acquired aplastic anemia (AA) who underwent hematopoietic stem cell transplantation (HSCT) with a fludarabine-based conditioning regimen from matched sibling donors (MSD) (n = 108) or haploidentical donors (HID) (n = 91) and immunosuppressive therapy (IST) (n = 188) from 2014 to 2020 at our hospital. Compared with HID-HSCT, MSD-HSCT had a lower incidence of graft failure (1% vs. 7%, p = 0.062), grade II–IV acute graft versus host disease (aGvHD) (16% vs. 35%, p = 0.001), and mild to severe chronic GvHD (cGvHD) (8% vs. 23%, p = 0.007), but an equivalent incidence of grade III–IV aGvHD (8% vs. 12%, p = 0.237) and moderate to severe cGvHD (3% vs. 9%, p = 0.076). HSCT had superior blood count recovery at 3, 6, and 12 months compared with IST (p < 0.001). The estimated 5-year overall survival (OS) of the MSD, HID, and IST groups were 86%, 72%, and 79% (p = 0.02), respectively; accordingly, the failure-free survival (FFS) rates were 85%, 68%, and 56%, respectively (p < 0.001). For patients aged ≤40 years, the OS rate was still significantly superior for MSD-HSCT receipients compared to HID-HSCT receipients (89% vs. 76%, p = 0.024) while the HID-HSCT recipients showed similar OS (76% vs. 78%, p = 0.166) but superior FFS (p = 0.047) when follow-up was longer than 14.5 months in contrast to IST. In a multivariate analysis, HID-HSCT and a conditioning regimen that included busulfan were adversely related to OS among patients who received allografts. In conclusion, MSD-HSCT was the frontline choice for patients with severe AA aged ≤40 years, while HID-HSCT was as effective as IST for patients without an MSD.